Geochronology and geochemistry of the Shanagen hydrothermal vein-type Mo deposit in Derbugan metallogenic belt of the NE China and their geological significance - Wu, Yunxia; Liu, Yu; Liu, Aoran; Tian, Lifu; Ye, Yasheng (Frontiers in Earth Science, 2023)
The Shanagen hydrothermal vein-type Mo deposit belongs to the Derbugan metallogenic belt, which is located in the Ergun block, NE China. The Mo mineralization is mainly developed in sericitized quartz siltstone around alkali-feldspar granite. In this paper, we present Molybdenite Re–Os dating, zircon U–Pb dating and geochemical data with the aim of determining metallogenic epoch and tectonic setting. Molybdenite Re–Os and zircon U–Pb dating of the alkali-feldspar granite indicate that the ore-formation and alkali-feldspar granite emplacement occurred at 143.1 ± 3.8 Ma, and 144.7±0.7 Ma. Both were formed in the early Early Cretaceous. Chemically, the alkali-feldspar granites are enriched in LREE and LILEs, depleted in HREE and HFSEs, and pronounced negative Eu anomalies, are metaluminous and belong to the high-K calc-alkaline series and highly differentiated I-type granite. Geochemical features and concave upwards REE pattern imply that alkali-feldspar granites were formed from magma generated by partial melting of lower crust. Combining the geochemistry, chronology, and the regional tectonic evolution, we infer that Shanagen hydrothermal vein-type Mo deposit was formed the extensional environment after the closure of the Mongol-Okhotsk Ocean.